Prognostic values of highly sensitive cardiac troponin T and B-type natriuretic peptide for clinical features in hypertrophic obstructive cardiomyopathy: a cross-sectional study. Issue 9 (17th September 2014) - Nakamura, Shunichi; Takano, Hitoshi; Matsuda, Junya; Chinen, Daigo; Kitamura, Mitsunobu; Murai, Koji; Asai, Kuniya; Yasutake, Masahiro; Takayama, Morimasa; Shimizu, Wataru
Abstract : Objectives: Although B-type natriuretic peptide (BNP) and highly sensitive cardiac troponin T (cTnT) are useful for the evaluation of clinical features in various cardiovascular diseases, there are comparatively few data regarding the utility of these parameters in patients with hypertrophic obstructive cardiomyopathy (HOCM). The goal of this study was to assess the association between BNP, cTnT and clinical parameters in patients with HOCM. Design: Cross-sectional survey Settings: The relationship between BNP, cTnT and clinical end points and echocardiographic data was investigated. Participants: This study included 102 consecutive outpatients with HOCM who were clinically stable. Results: BNP was significantly associated with both maximum left ventricular (LV) wall thickness (r=0.28; p=0.003), and septal peak early transmitral filling velocity/peak early diastolic mitral annulus velocity (r=0.51; p=0.0001). No statistically significant associations were seen between cTnT and any echocardiographic parameters, but the presence of atrial fibrillation (AF) was associated with a high level of cTnT (p=0.01). Conclusions: BNP is useful for monitoring clinical parameters and as a reflection of both LV systolic/diastolic function and increased LV pressure in patients with HOCM. A high level of serum cTnT is associated with the presence of AF.